1984
DOI: 10.1139/v84-160
|View full text |Cite
|
Sign up to set email alerts
|

Some chemical and analytical aspects of polysaccharide modifications. IV. Electron spin resonance studies of nitroxide-labelled chitin and chitosan derivatives

Abstract: Nitroxide spin labels have been attached to chitin, chitosan, and their derivatives in order to investigate the solution and gel characteristics of these polymers. Thus, chitin was nonselectively acylated using the chloroacetamide label 3 to afford. the corresponding nitroxide derivative 4. Selective and nonselective labelling of chitosan was accomplished either via reductive alkylation using the keto label 5 and sodium cyanoborohydride or via a chitosan sulfate intermediate using labels 3 or 5. Two branched w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…63 These results can be considered to depend on microscopic changes in the gel structure63 as well as on changes from a threefold double helix of the solid state to larger aggregates in the gel state arising from inter helix packing and formation of bundles.49,71 Some interesting ESR results were obtained for the spin-labeled chitin 214, chitosan 207 and 215, and their water-soluble analogues 204, 205, and 208. 54,58 The rc value for the chitin derivative 214 (Table V) was considerably smaller than those obtained for the chitosan derivatives. This result was attributed to the fact that chitin was labeled under heterogeneous conditions in which the ds was lower (0.04), but the label was attached mostly to the surface of the biopolymer.58 Consequently this surface labeling allows more rotational mobility for the spin label while the polymer motion (tc > 100 ns) would make no contribution on the ESR time scale.…”
Section: Nonspecific Reactionsmentioning
confidence: 75%
See 4 more Smart Citations
“…63 These results can be considered to depend on microscopic changes in the gel structure63 as well as on changes from a threefold double helix of the solid state to larger aggregates in the gel state arising from inter helix packing and formation of bundles.49,71 Some interesting ESR results were obtained for the spin-labeled chitin 214, chitosan 207 and 215, and their water-soluble analogues 204, 205, and 208. 54,58 The rc value for the chitin derivative 214 (Table V) was considerably smaller than those obtained for the chitosan derivatives. This result was attributed to the fact that chitin was labeled under heterogeneous conditions in which the ds was lower (0.04), but the label was attached mostly to the surface of the biopolymer.58 Consequently this surface labeling allows more rotational mobility for the spin label while the polymer motion (tc > 100 ns) would make no contribution on the ESR time scale.…”
Section: Nonspecific Reactionsmentioning
confidence: 75%
“…Studies with gels of compound 207 revealed a complex ESR spectrum that seemed to indicate two nitroxyl populations.54,58 When 207 was subjected to a watermethanol-water solvent cycle over a 2-week period, the ESR changed to a simple three-line spectrum. 58 In this case the mobile nitroxyl population completely predominated, indicating a structural reorganization allowing more spin label to have access to the solvent.…”
Section: Nonspecific Reactionsmentioning
confidence: 92%
See 3 more Smart Citations